Needs Analysis on the Improvement of English for Informatics Courses Based on the Perception of Non-English Teachers of State Polytechnic of Malang - Asri, Atiqah Nurul; Ulfa, Farida; Suryadi, Satrio Binusa (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
The purpose of the present study was to reveal the needs analysis commissioned by the Information Technology Department regarding the non-English teachers’ perceptions on the teaching and learning practices of the English language in the department. The study employed an online questionnaire and interview to 23 IT teachers. The questionnaire covered the five categories, namely English Language Teaching at IT Department, Language Skills and Components, Teaching Learning Activities, Teaching Skills, IT related topics should be included and Assessments. It used Likert Scale ranging from 1-4 showing disagree to really agree. In addition, the interview utilized a prompt designed beforehand to get the necessary advice to formulate appropriate English language materials for IT students. The results revealed that the teachers needed a more efficient course design and development covering the design of the course syllabus, the creation of activities and materials, and the evaluation of learner progress. They are expected to provide insights as the basis for the improvement both on the teaching preparation and practices